Efficient lithium supplement material and preparation method and application thereof
By uniformly mixing the lithium source material, carbon source material and conductive carbon in the lithium-ion battery positive electrode material and high-temperature treatment to form a lithium-rich material and a carbon matrix with a pore structure, the problems of unstable structure and low conductivity of the existing positive electrode material are solved, and the preparation of efficient lithium supplement materials is achieved, and the capacity and rate performance of the battery are improved.
Patent Information
- Application Number
- CN202311106557.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-30
- Publication Date
- 2025-02-28
AI Technical Summary
The structure of the existing lithium-ion battery positive electrode material is unstable, the lithium supplement capacity is small, and the conductivity is low, which limits its application. The existing solutions are costly and complex, making it difficult to produce on a large scale.
By uniformly mixing the lithium source material, the carbon source material and the conductive carbon in a solvent, drying and sintering treatment at high temperatures, a lithium-rich material and a carbon matrix with a pore structure are formed, lithium oxide and conductive carbon are evenly distributed, and a carbon cladding layer is formed on the surface to prepare an efficient lithium supplement material.
It improves the stability and rate performance of lithium supplement materials, provides a larger lithium supplement capacity, simplifies the process, reduces costs, and is suitable for large-scale production.
Smart Images

Figure CN119542419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery materials, and in particular to a high-efficiency lithium supplement material and a preparation method and application thereof. Background Art
[0002] As an important new energy storage device, lithium-ion batteries are widely used in mobile communications, electric vehicles, renewable energy and other fields. Among them, the positive electrode material of lithium-ion batteries plays a vital role and directly affects the performance and cycle life of the battery.
[0003] Among the positive electrode materials of lithium-ion batteries, lithium supplement materials are often used to improve the lithium ion storage function of the battery cell, such as lithium cobalt oxide, lithium manganese oxide, etc. However, the commonly used lithium supplement materials have problems such as unstable structure, small lithium supplement capacity, and low conductivity, which limit their application in lithium-ion batteries.
[0004] In order to improve these problems, some solutions have been proposed in the prior art. For example, by changing the structure and composition of lithium-supplementing materials, or adding conductive agents to improve the conductivity and cycle stability of materials. However, these solutions have the problems of high cost, complex process, and difficulty in large-scale production, which limits their promotion in industrial applications. Summary of the invention
[0005] The present invention provides a high-efficiency lithium supplement material and a preparation method and application thereof, with the aim of providing a lithium supplement material that can improve the stability and rate performance of the lithium supplement material while providing a lithium supplement material with a larger lithium supplement capacity, and solving the problems of complex process and high cost in the prior art.
[0006] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a high-efficiency lithium supplement material, the preparation method comprising:
[0007] Placing a lithium source material, a carbon source material, a conductive carbon and a solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution;
[0008] The mixed solution is placed in a drying device for drying at a temperature of 60°C-300°C to remove the solvent to obtain an intermediate material;
[0009] The intermediate material is placed in a sintering device under an inert gas environment, and the temperature is raised to 600°C-1300°C at a heating rate of 1°C / min-5°C / min, and a pre-sintering treatment is performed for 2 hours-8 hours, so that the lithium source material is decomposed into an active lithium-rich material with a particle size D50 of 0.1nm-150nm, and the carbon source material is etched at the same time, and finally grows in the gaps, pores and surface of the carbon matrix after the carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps, pores and surface of the carbon matrix to form a core material;
[0010] After adjusting the temperature of the sintering equipment to 600°C-1400°C, a carbon-containing gas is introduced into the sintering equipment at the same time, and the temperature is kept for 3 hours-24 hours to form a carbon coating layer on the surface of the above-mentioned core material. After cooling to room temperature, the material is discharged to obtain a high-efficiency lithium supplement material.
[0011] Preferably, the lithium source material includes: one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, lithium formate, lithium metasilicate, lithium orthosilicate, lithium phosphate or lithium carbide; the lithium-rich material includes lithium oxide;
[0012] The carbon source material includes: one or more of sucrose, glucose, starch, fructose, cellulose, phenolic resin, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, and polyethylene glycol;
[0013] The conductive carbon includes: one or more of carbon fiber, carbon nanotube, and graphene;
[0014] The solvent: one or more of deionized water, ethanol, N-methylpyrrolidone, and acetone;
[0015] The solid content of the mixed solution is 10wt%-45wt%.
[0016] Preferably, the mass of the lithium source material accounts for 35%-75% of the total mass of the mixed solution;
[0017] The mass of the carbon source material accounts for 20%-65% of the total mass of the mixed solution;
[0018] The mass of the conductive carbon accounts for 0.1-15% of the total mass of the mixed solution.
[0019] Preferably, the stirring equipment includes: one or more of a magnetic stirrer, a VC high-efficiency mixer, a planetary mixer, and a vertical stirring tank;
[0020] The drying equipment includes: one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying treatment temperature is 60° C.-300° C.; and the drying time is 6 hours-24 hours.
[0021] Preferably, the sintering equipment includes: one or more of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln.
[0022] Preferably, the inert gas includes: one or more of nitrogen, argon, and helium;
[0023] The flow rate of the inert gas is between 0.5L / min and 10.0L / min;
[0024] The carbon-containing gas includes any one of acetylene, methane and propane;
[0025] The mixed gas ratio of the carbon-containing gas to the inert gas is 1:[0.25-3.0].
[0026] In a second aspect, an embodiment of the present invention provides a high-efficiency lithium supplement material prepared by the preparation method described in the first aspect above.
[0027] Preferably, the efficient lithium supplement material comprises: a carbon matrix, lithium oxide and conductive carbon filled in the gaps, pores and on the surface of the carbon matrix, and a carbon coating layer coated on the outermost surface of the carbon matrix;
[0028] The mass of the carbon matrix accounts for 15%-60% of the total mass of the high-efficiency lithium supplement material;
[0029] The mass of the lithium oxide accounts for 35%-75% of the total mass of the high-efficiency lithium supplement material;
[0030] The mass of the conductive carbon accounts for 0.1%-15% of the total mass of the efficient lithium supplement material;
[0031] The mass of the carbon coating layer accounts for 0.2%-10% of the total mass of the high-efficiency lithium supplement material.
[0032] In a third aspect, an embodiment of the present invention provides a positive electrode plate, wherein the positive electrode plate includes the high-efficiency lithium supplement material described in the second aspect.
[0033] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet described in the third aspect.
[0034] The preparation method of the efficient lithium supplement material provided by the embodiment of the present invention can realize molecular-level uniform mixing of lithium source material and carbon source material in a solvent, and react with each other at high temperature, so that the lithium source material can be decomposed to generate lithium-rich material lithium oxide with smaller particle size and higher activity, so that the material can provide more active lithium, and at the same time, the carbon source material is etched. After carbonization and etching, the carbon source material forms a carbon matrix with a porous structure, and lithium oxide and conductive carbon are evenly distributed in the gaps, pores and surface of the carbon matrix, thereby forming a core material, and a carbon layer is coated on the surface of the core material to finally obtain a efficient lithium supplement material. The preparation method of the present invention is simple to operate, and the carbon source material used to prepare the carbon matrix is not only widely available and low in cost, but also has a partial template effect, which simplifies the porous carbon matrix preparation process, improves the preparation efficiency, and has good economic benefits.
[0035] In the high-efficiency lithium-supplementing material provided by the embodiment of the present invention, the carbon source material forms a carbon matrix after sintering. The main function of the carbon matrix is to isolate the aggregation of the lithium source material and prevent it from agglomerating to form large particles, so that the lithium source material can be better decomposed into lithium oxide and can be evenly distributed in the gaps, pores and surface of the carbon matrix. At the same time, it can inhibit the expansion of lithium oxide during the cycle, reduce the contact between lithium oxide and the electrolyte, reduce the occurrence of side reactions, and inhibit the formation of lithium dendrites. In addition, conductive carbon is also distributed in the gaps, pores and surface of the carbon matrix, so that the high-efficiency lithium-supplementing material of the present invention has higher conductivity, thereby improving the rate performance.
[0036] The high-efficiency lithium supplement material prepared by the preparation method of the present invention is applied in lithium-ion batteries, so that the lithium-ion batteries can have higher capacity and better rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 A flow chart of a method for preparing a high-efficiency lithium supplement material provided by an embodiment of the present invention;
[0038] Figure 2 The charge and discharge curve diagram of the button battery assembled in Example 1 of the present invention;
[0039] Figure 3 This is a comparison chart of rate cycle tests of button-type batteries assembled in Example 2 of the present invention and in Comparative Example 1;
[0040] Figure 4 It is a comparison chart of the charge and discharge curves of button-type batteries assembled in Example 3 of the present invention and in Comparative Example 1. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are for a better understanding of the present invention, are not limited to the best mode of implementation, and do not limit the content and protection scope of the present invention. Any product that is the same or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the present invention with the features of other prior arts shall fall within the protection scope of the present invention.
[0042] The present invention provides a method for preparing a highly efficient lithium supplement material. Figure 1 As shown, the specific steps include:
[0043] Step 110, placing the lithium source material, the carbon source material, the conductive carbon and the solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution;
[0044] The lithium source material includes one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, lithium formate, lithium metasilicate, lithium orthosilicate, lithium phosphate or lithium carbide; the mass of the lithium source material accounts for 35%-75% of the total mass of the mixed solution;
[0045] The carbon source material includes: one or more of sucrose, glucose, starch, fructose, cellulose, phenolic resin, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, and polyethylene glycol; the mass of the carbon source material accounts for 20%-65% of the total mass of the mixed solution;
[0046] The conductive carbon includes: one or more of carbon fiber, carbon nanotube, and graphene; the mass of the conductive carbon accounts for 0.1-15% of the total mass of the mixed solution;
[0047] Solvent: one or more of deionized water, ethanol, N-methylpyrrolidone, and acetone;
[0048] The mixing equipment includes: one or more of a magnetic stirrer, a VC high-efficiency mixer, a planetary mixer, and a vertical mixing tank;
[0049] The solid content of the obtained mixed solution is 10wt%-45wt%.
[0050] Step 120, placing the mixed solution in a drying device for drying at a temperature of 60° C. to 300° C. to remove the solvent and obtain an intermediate material;
[0051] The drying equipment includes one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying temperature is 60°C-300°C; and the drying time is 6 hours-24 hours.
[0052] Step 130, placing the intermediate material in a sintering device under an inert gas environment, heating the temperature to 600°C-1300°C at a heating rate of 1°C / min-5°C / min, and pre-sintering for 2 hours-8 hours, so that the lithium source material is decomposed into an active lithium-rich material with a particle size D50 of 0.1nm-150nm, and at the same time, the carbon source material is etched, and finally grows in the gaps, pores and surface of the carbon matrix after the carbon source material is carbonized and etched, and the conductive carbon is evenly distributed in the gaps, pores and surface of the carbon matrix to form a core material;
[0053] The sintering equipment includes: one or more of a box furnace, a tube furnace, a pusher furnace, a roller kiln, and a rotary kiln;
[0054] The formed lithium-rich material mainly includes lithium oxide.
[0055] The inert gas includes: one or more of nitrogen, argon, and helium; the flow rate of the inert gas is between 0.5 L / min and 10.0 L / min.
[0056] Step 140, after adjusting the temperature of the sintering equipment to 600° C.-1400° C., a carbon-containing gas is introduced into the sintering equipment, and the temperature is kept for 3 hours-24 hours to form a carbon coating layer on the surface of the core material, and the material is discharged after cooling to room temperature to obtain a high-efficiency lithium supplement material;
[0057] The carbon-containing gas includes any one of acetylene, methane and propane; the flow rate of the carbon-containing gas is between 0.5L / min and 10.0L / min;
[0058] After the carbon-containing gas is introduced into the sintering equipment, a mixed gas of the carbon-containing gas and the inert gas is formed, wherein the volume ratio of the carbon-containing gas to the inert gas is 1:[0.25-3.0].
[0059] The high-efficiency lithium supplement material prepared by the above preparation method in the embodiment of the present invention includes: a carbon matrix, lithium oxide and conductive carbon filled in the gaps, pores and on the surface of the carbon matrix, and a carbon coating layer coated on the outermost surface of the carbon matrix.
[0060] The mass of the carbon matrix accounts for 15% to 60% of the total mass of the high-efficiency lithium supplement material;
[0061] The mass of lithium oxide accounts for 35%-75% of the total mass of the high-efficiency lithium supplement material;
[0062] The mass of the conductive carbon accounts for 0.1%-15% of the total mass of the efficient lithium supplement material;
[0063] The mass of the carbon coating layer accounts for 0.2%-10% of the total mass of the high-efficiency lithium supplement material.
[0064] In the present application, the carbon source material forms a carbon matrix after sintering. The main function of the carbon matrix is to isolate the aggregation of the lithium source material and prevent it from agglomerating to form large particles. The lithium source material can be better decomposed to obtain lithium oxide and evenly distributed in the gaps, pores and surface of the carbon matrix. At the same time, it can inhibit the expansion of lithium oxide during the cycle, reduce the contact between lithium oxide and electrolyte, reduce the occurrence of side reactions, and inhibit the formation of lithium dendrites.
[0065] In the present application, the above-mentioned etching effect on the carbon source material is mainly due to the fact that the lithium source material is highly corrosive in a high-temperature alkaline environment during the high-temperature decomposition into an active lithium-rich material, thereby etching the surface of the carbon source material to form a carbon matrix with a porous structure on the surface.
[0066] In the present application, conductive carbon is distributed in the gaps, pores and on the surface of the carbon matrix, so that the high-efficiency lithium supplement material of the present invention has higher conductivity, thereby improving the rate performance.
[0067] The high-efficiency lithium supplement material provided in the embodiment of the present invention can be used as an additive for positive electrode active materials, and can be used together with commonly used positive electrode active materials, conductive agents, and binders to prepare positive electrode sheets.
[0068] A positive electrode plate containing a high-efficiency lithium supplement material can be assembled with a separator, an electrolyte or a solid electrolyte, and a negative electrode plate to form a lithium-ion battery.
[0069] Among them, the diaphragm includes but is not limited to any one of a double-sided alumina diaphragm and a diaphragm containing a sodium ion solid electrolyte; the base film of the diaphragm includes: any one of a polyolefin film, a non-woven fabric diaphragm, a fiber diaphragm, and a polyaramid diaphragm; the negative electrode plate includes any one of a lithium plate or a negative electrode current collector containing a negative electrode active material; specifically, the negative electrode current collector includes but is not limited to aluminum foil, copper foil or titanium foil, and in addition, the active material layer on the surface of the negative electrode current collector also contains commonly used conductive agents and binders.
[0070] The lithium-ion battery containing the high-efficiency lithium-supplementing material provided by the embodiment of the present invention can provide more active lithium ions in the lithium-rich material in the high-efficiency lithium-supplementing material during the cycle, so that the lithium-ion battery has a higher capacity, and the conductive carbon in the high-efficiency lithium-supplementing material can improve the rate performance of the lithium-ion battery; the presence of pores on the surface of the carbon matrix in the high-efficiency lithium-supplementing material of the present invention can inhibit the expansion of the lithium-rich material during the cycle, thereby improving the stability of the material; in addition, the lithium ions decomposed from the lithium-rich material in the gaps of the carbon matrix are easier to diffuse, thereby increasing the diffusion rate of lithium ions in the bulk phase, thereby improving the cycle performance of the lithium-ion battery; furthermore, the carbon coating layer of the high-efficiency lithium-supplementing material can prevent the material from directly contacting the electrolyte and reduce the occurrence of side reactions.
[0071] Therefore, the structural particularity of the high-efficiency lithium supplement material of the present invention can improve the specific capacity, rate performance and cycle performance of lithium-ion batteries through the synergistic effect of the above-mentioned multi-faceted material composition.
[0072] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the high-efficiency lithium supplement material of the present invention are respectively described below with multiple specific examples.
[0073] Example 1
[0074] This embodiment provides a preparation process and performance test of an efficient lithium supplement material, and the specific process is as follows:
[0075] (1) Glucose, graphene, lithium hydroxide and deionized water are added to a VC high-efficiency mixer, and stirred to mix evenly to obtain a mixed solution with a solid content of 22 wt%; wherein the content of each solid component in the mixed solution is: 35 wt% glucose, 8 wt% graphene, and 57 wt% lithium hydroxide.
[0076] (2) The mixed solution was placed in a forced air drying oven and dried at 80° C. for 12 hours to remove the solvent and obtain an intermediate material.
[0077] (3) The intermediate material is placed in a rotary kiln under an argon gas environment, and the temperature is raised to 800°C at a heating rate of 2°C / min, and pre-sintered for 5 hours to decompose the lithium source material into an active lithium-rich material with a particle size D50 of 30 nm, while etching the carbon source material. Finally, the intermediate material grows in the gaps and on the surface of the carbon matrix after carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps and on the surface of the carbon matrix to form a core material; wherein the flow rate of the argon gas is 2.4 L / min.
[0078] (4) The rotary kiln is further heated to 950°C at a rate of 2°C / min, and acetylene gas containing carbon is introduced into the rotary kiln at a flow rate of 2.4 L / min. The volume ratio of acetylene to argon is 1:2. The kiln is kept warm for 5 hours to form a carbon coating layer on the surface of the core material. The material is then cooled to room temperature and discharged to obtain a high-efficiency lithium supplement material having a carbon coating layer thickness of 1.7 nm.
[0079] The high-efficiency lithium supplement material prepared in Example 1 of the present invention was used to prepare a positive electrode sheet and assembled into a button cell for testing. The preparation process and the testing process are as follows:
[0080] Preparation of positive electrode sheet: The high-efficiency lithium supplement material, polyvinylidene fluoride (PVDF) and conductive carbon black (SP) prepared in this embodiment are homogenized into a slurry in a mass ratio of 90:5:5, and then coated on aluminum foil to prepare a positive electrode sheet.
[0081] Assembly of button cells: A positive electrode sheet coated with the high-efficiency lithium supplement material prepared in this embodiment, a polypropylene PP separator, a hard carbon negative electrode sheet and a 1M Li PF6 electrolyte are assembled into a button cell using conventional methods.
[0082] The button battery test method is: charge at a constant current rate of 0.1C to a voltage of 4.6V, then charge at a constant voltage of 4.6V to 0.02C, then let it stand for 5 minutes, and then discharge at a constant current rate of 0.1C to a voltage of 3.0V. Perform the first week of charge and discharge test. The test charge and discharge curve is as follows: Figure 2 As shown, the charge specific capacity of the battery assembled in this embodiment is 509 mAh / g, which indicates that the high-efficiency lithium replenishing material prepared in this embodiment of the present invention has an obvious lithium replenishing effect, and the material can provide more active lithium.
[0083] Example 2
[0084] This embodiment provides a preparation process and performance test of an efficient lithium supplement material, and the specific process is as follows:
[0085] (1) Glucose, graphene, lithium hydroxide and deionized water are added to a magnetic stirrer, and stirred and mixed to obtain a mixed solution with a solid content of 25 wt %; wherein the content of each solid component in the mixed solution is: 50 wt % glucose, 5 wt % graphene and 45 wt % lithium hydroxide.
[0086] (2) The mixed solution was placed in a forced air drying oven and dried at 90° C. for 8 hours to remove the solvent and obtain an intermediate material.
[0087] (3) The intermediate material is placed in a tubular furnace under an argon gas environment, and the temperature is raised to 850°C at a heating rate of 2°C / min, and a pre-sintering treatment is performed for 5 hours to decompose the lithium source material into an active lithium-rich material with a particle size D50 of 50 nm, and at the same time, the carbon source material is etched. Finally, the intermediate material grows in the gaps and on the surface of the carbon matrix after carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps and on the surface of the carbon matrix to form a core material; wherein the flow rate of the argon gas is 2L / min.
[0088] (4) After the tubular furnace is heated to 1000°C at a rate of 2°C / min, acetylene, a carbon-containing gas, is introduced into the tubular furnace at a flow rate of 2 L / min, and the volume ratio of acetylene to argon is 1:1. The temperature is kept for 3 hours to form a carbon coating layer on the surface of the core material. After cooling to room temperature, the material is discharged to obtain a high-efficiency lithium supplement material with a carbon coating layer thickness of 1.3 nm.
[0089] The high-efficiency lithium supplement material prepared in Example 2 of the present invention is used as an additive for the positive electrode material, and is mixed with a lithium cobalt oxide positive electrode material at a mass ratio of 5:95 to form a positive electrode active material, and then mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (SP) at a mass ratio of 90:5:5 to form a slurry, thereby preparing a positive electrode sheet and assembling it into a button cell for testing. The preparation process of the battery is the same as the method in Example 1.
[0090] The rate performance of the button cell assembled in this embodiment was tested, and the specific method was as follows: the specific method was as follows: first, the battery was charged to 4.4V at a rate of 0.1C, and then the current was reduced to 0.05C at a constant voltage of 4.4V, and then the battery was discharged to 2.75V at a rate of 0.1C, and the cycle was repeated for 5 cycles; then, the battery was charged to 4.4V at a rate of 0.2C, and then the current was reduced to 0.05C at a constant voltage of 4.4V, and then the battery was discharged to 2.75V at a rate of 0.2C, and the cycle was repeated for 5 cycles; then, the battery was charged to 4.4V at a rate of 0.5C, and then the current was reduced to 0.05C at a constant voltage of 4.4V, and then the battery was discharged to 2.75V at a rate of 0.5C, and the cycle was repeated for 5 cycles; then, the battery was charged to 4.4V at a rate of 1C, and then the current was reduced to 0.05C at a constant voltage of 4.4V, and then the battery was discharged to 2.75V at a rate of 1C, and then the battery was charged to 4.4V ... the battery was
[0091] The rate cycle test diagram of the button cell of Example 2 is as follows: Figure 3 shown.
[0092] Example 3
[0093] This embodiment provides a preparation process and performance test of an efficient lithium supplement material, and the specific process is as follows:
[0094] (1) Glucose, graphene, lithium hydroxide and deionized water are added to a magnetic stirrer, and stirred and mixed to obtain a mixed solution with a solid content of 16 wt %; wherein the content of each solid component in the mixed solution is: 30 wt % glucose, 10 wt % graphene and 60 wt % lithium hydroxide.
[0095] (2) The mixed solution was placed in a forced air drying oven and dried at 90° C. for 12 hours to remove the solvent and obtain an intermediate material.
[0096] (3) The intermediate material is placed in a tubular furnace under an argon gas environment, and the temperature is raised to 880°C at a heating rate of 2°C / min, and a pre-sintering treatment is performed for 3 hours to decompose the lithium source material into an active lithium-rich material with a particle size D50 of 100 nm, and at the same time, the carbon source material is etched. Finally, the intermediate material grows in the gaps and on the surface of the carbon matrix after carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps and on the surface of the carbon matrix to form a core material; wherein the flow rate of the argon gas is 1.2 L / min.
[0097] (4) The temperature of the tubular furnace is further raised to 1000°C at a rate of 2°C / min, and acetylene gas containing carbon is introduced into the tubular furnace at a flow rate of 1.5 L / min. The volume ratio of acetylene to argon is 1:2. The temperature is kept at this temperature for 8 hours to form a carbon coating layer on the surface of the core material. The material is then cooled to room temperature and discharged to obtain a high-efficiency lithium supplement material having a carbon coating layer thickness of 2.1 nm.
[0098] The high-efficiency lithium supplement material prepared in Example 3 of the present invention is used as an additive for the positive electrode material, and is mixed with a lithium cobalt oxide positive electrode material at a mass ratio of 5:95 to form a positive electrode active material, and then mixed with polyvinylidene fluoride (PVDF) and conductive carbon black (SP) at a mass ratio of 90:5:5 to form a slurry, thereby preparing a positive electrode sheet and assembling it into a button cell for testing. The preparation process of the battery is the same as the method in Example 1.
[0099] The button battery test method is: charge at a constant current rate of 0.1C to a voltage of 4.4V, then charge at a constant voltage of 4.4V to 0.02C, then let it stand for 5 minutes, and then discharge at a constant current rate of 0.1C to a voltage of 2.75V for the first week of charge and discharge test. The first week of charge and discharge test curve is as follows Figure 4 shown.
[0100] Example 4
[0101] This embodiment provides a preparation process and performance test of an efficient lithium supplement material, and the specific process is as follows:
[0102] (1) Glucose, graphene and lithium hydroxide are added together with deionized water into a VC high-efficiency mixer, and stirred and mixed evenly to obtain a mixed solution with a solid content of 20wt%; wherein the content of each solid component in the mixed solution is: 35wt% glucose, 8wt% graphene, and 57wt% lithium hydroxide.
[0103] (2) The mixed solution was placed in a forced air drying oven and dried at 85° C. for 8 hours to remove the solvent and obtain an intermediate material.
[0104] (3) The intermediate material is placed in a rotary kiln under an argon gas environment, and the temperature is raised to 930°C at a heating rate of 2°C / min, and a pre-sintering treatment is performed for 4 hours to decompose the lithium source material into an active lithium-rich material with a particle size D50 of 120 nm, and at the same time, the carbon source material is etched. Finally, the intermediate material grows in the gaps and on the surface of the carbon matrix after carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps and on the surface of the carbon matrix to form a core material; wherein the flow rate of the argon gas is 1.6 L / min.
[0105] (4) After the temperature of the rotary kiln is further adjusted to 900° C., acetylene containing carbon is introduced into the rotary kiln at a flow rate of 1.6 L / min, and the volume ratio of acetylene to argon is 1:3. The temperature is kept for 6 hours to form a carbon coating layer on the surface of the core material. After cooling to room temperature, the material is discharged to obtain a high-efficiency lithium supplement material with a carbon coating layer thickness of 0.9 nm.
[0106] In order to better illustrate the effects of the embodiments of the present invention, comparative example 1 is compared with embodiments 2-3.
[0107] Comparative Example 1
[0108] In this comparative example, a positive electrode sheet coated with a lithium cobalt oxide positive electrode material, a polypropylene PP separator, a hard carbon negative electrode sheet and a 1M Li PF6 electrolyte were selected and assembled into a button battery using the same method as in Example 1.
[0109] The rate performance was tested according to the test method of Example 2, and the rate cycle test curve was obtained as shown in Figure 3 As shown; the first week charge and discharge test is carried out according to the test method of Example 3, and the first week charge and discharge curve is as shown Figure 4 shown.
[0110] The button cells of Examples 2 and 3 contain high-efficiency lithium replenishing materials. The rate performance of Example 2 and the first-week coulombic efficiency of Example 3 are significantly higher than those of the button cell of Comparative Example 1, indicating that the high-efficiency lithium replenishing material contained in the present invention provides more active lithium for the battery. Therefore, the high-efficiency lithium replenishing material of the present invention has better rate performance and first-week coulombic efficiency.
[0111] The preparation method of the efficient lithium supplement material provided by the embodiment of the present invention can realize molecular-level uniform mixing of lithium source material and carbon source material in a solvent, and react with each other at high temperature, so that the lithium source material can be decomposed to generate lithium-rich material lithium oxide with smaller particle size and higher activity, so that the material can provide more active lithium, and at the same time, the carbon source material is etched. After carbonization and etching, the carbon source material forms a carbon matrix with a porous structure, and lithium oxide and conductive carbon are evenly distributed in the gaps, pores and surface of the carbon matrix, thereby forming a core material, and a carbon layer is coated on the surface of the core material to finally obtain a efficient lithium supplement material. The preparation method of the present invention is simple to operate, and the carbon source material used to prepare the carbon matrix is not only widely available and low in cost, but also has a partial template effect, which simplifies the porous carbon matrix preparation process, improves the preparation efficiency, and has good economic benefits.
[0112] In the high-efficiency lithium-supplementing material provided by the embodiment of the present invention, the carbon source material forms a carbon matrix after sintering. The main function of the carbon matrix is to isolate the aggregation of the lithium source material and prevent it from agglomerating to form large particles, so that the lithium source material can be better decomposed into lithium oxide and can be evenly distributed in the gaps, pores and surface of the carbon matrix. At the same time, it can inhibit the expansion of lithium oxide during the cycle, reduce the contact between lithium oxide and the electrolyte, reduce the occurrence of side reactions, and inhibit the formation of lithium dendrites. In addition, conductive carbon is also distributed in the gaps, pores and surface of the carbon matrix, so that the high-efficiency lithium-supplementing material of the present invention has higher conductivity, thereby improving the rate performance.
[0113] The high-efficiency lithium supplement material prepared by the preparation method of the present invention is applied in lithium-ion batteries, so that the lithium-ion batteries can have higher capacity and better rate performance.
[0114] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing an efficient lithium supplement material, characterized in that: The preparation method comprises: Placing a lithium source material, a carbon source material, a conductive carbon and a solvent in a stirring device, stirring and mixing them uniformly to obtain a mixed solution; The mixed solution is placed in a drying device for drying at a temperature of 60°C-300°C to remove the solvent to obtain an intermediate material; The intermediate material is placed in a sintering device under an inert gas environment, and the temperature is raised to 600°C-1300°C at a heating rate of 1°C / min-5°C / min, and a pre-sintering treatment is performed for 2 hours-8 hours, so that the lithium source material is decomposed into an active lithium-rich material with a particle size D50 of 0.1nm-150nm, and the carbon source material is etched at the same time, and finally grows in the gaps, pores and surface of the carbon matrix after the carbonization and etching of the carbon source material, and the conductive carbon is evenly distributed in the gaps, pores and surface of the carbon matrix to form a core material; After adjusting the temperature of the sintering equipment to 600°C-1400°C, a carbon-containing gas is introduced into the sintering equipment at the same time, and the temperature is kept for 3 hours-24 hours to form a carbon coating layer on the surface of the above-mentioned core material. After cooling to room temperature, the material is discharged to obtain a high-efficiency lithium supplement material.
2. The high-efficiency lithium supplement material according to claim 1, characterized in that: The lithium source material includes: one or more of lithium hydroxide, lithium oxide, lithium carbonate, lithium oxalate, lithium acetate, lithium formate, lithium metasilicate, lithium orthosilicate, lithium phosphate or lithium carbide; the lithium-rich material includes lithium oxide; The carbon source material includes: one or more of sucrose, glucose, starch, fructose, cellulose, phenolic resin, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, and polyethylene glycol; The conductive carbon includes: one or more of carbon fiber, carbon nanotube, and graphene; The solvent: one or more of deionized water, ethanol, N-methylpyrrolidone, and acetone; The solid content of the mixed solution is 10wt%-45wt%.
3. The high-efficiency lithium supplement material according to claim 1, characterized in that: The mass of the lithium source material accounts for 35%-75% of the total mass of the mixed solution; The mass of the carbon source material accounts for 20%-65% of the total mass of the mixed solution; The mass of the conductive carbon accounts for 0.1-15% of the total mass of the mixed solution.
4. The high-efficiency lithium supplement material according to claim 1, characterized in that: The stirring equipment includes: one or more of a magnetic stirrer, a VC high-efficiency mixer, a planetary mixer, and a vertical stirring tank; The drying equipment includes: one or more of a blast drying oven, an oil bath pot, a spray dryer, and a vacuum drying oven; the drying treatment temperature is 60° C.-300° C.; and the drying time is 6 hours-24 hours.
5. The high-efficiency lithium supplement material according to claim 1, characterized in that: The sintering equipment includes: one or more of a box furnace, a tube furnace, a push plate furnace, a roller kiln, and a rotary kiln.
6. The high-efficiency lithium supplement material according to claim 1, characterized in that: The inert gas includes: one or more of nitrogen, argon, and helium; The flow rate of the inert gas is between 0.5L / min and 10.0L / min; The carbon-containing gas includes any one of acetylene, methane and propane; The mixed gas ratio of the carbon-containing gas to the inert gas is 1:[0.25-3.0].
7. A high-efficiency lithium supplement material prepared by the preparation method according to any one of claims 1 to 6.
8. The high-efficiency lithium supplement material according to claim 7, characterized in that: The high-efficiency lithium supplement material comprises: a carbon matrix, lithium oxide and conductive carbon filled in the gaps, pores and on the surface of the carbon matrix, and a carbon coating layer coated on the outermost surface of the carbon matrix; The mass of the carbon matrix accounts for 15%-60% of the total mass of the high-efficiency lithium supplement material; The mass of the lithium oxide accounts for 35%-75% of the total mass of the high-efficiency lithium supplement material; The mass of the conductive carbon accounts for 0.1%-15% of the total mass of the efficient lithium supplement material; The mass of the carbon coating layer accounts for 0.2%-10% of the total mass of the high-efficiency lithium supplement material.
9. A positive electrode sheet, characterized in that: The positive electrode plate comprises the high-efficiency lithium supplement material described in any one of claims 7-8 above.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as described in claim 9 above.
Citation Information
Patent Citations
Positive plate, lithium-ion battery positive lithium-supplementing material and preparation method of material
CN109786746A
Lithium supplement additive, and preparation method and application thereof
CN113793983A
Core-shell binary positive electrode lithium supplement additive and preparation method and application thereof
CN115692697A
Positive electrode lithium supplementing material and preparation method and application thereof
CN116598494A